Using Multimedia Interactive Web Blog Science Virtual Laboratory to Improve Students' Critical Thinking and Concept Mastery - Andriani, Aldina Eka; Sulistyorini, Sri; Sunarso, Ali (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The presence and condition of laboratories are critical factors in the success of learning activities through practical work, thereby improving student motivation and interest in learning. This research aims to determine the utilization of a virtual laboratory in improving critical thinking skills and mastery of science concepts for Elementary School Teacher Education (PGSD) students. The research used an experimental method utilizing a quasi-experimental design, specifically a nonequivalent control group design. Purposive sampling was the chosen sampling technique, and the research sample comprised 42 second-semester students from the Elementary School Teacher Education Department enrolled in the Elementary School Science Laboratory course. The samples were intentionally divided into two groups: Group K, the experimental group, and Group O, the control group. A multiple-choice test served as the data collection instrument. The collected data were analyzed using the N-Gain formula and t-test. The N-Gain results for concept mastery in the experimental group are 0.5%, and in the control group, it is 0.3%. Meanwhile, the average score for critical thinking skills in the experimental group is 80.77, and the average score for the control group is 76.31. Therefore, using a virtual laboratory affects students' mastery of concepts and critical thinking skills in Natural Science.